Cannabidiol Reduces Leukemic Cell Size – But Is It Important? - Kalenderoglou, Nikoletta; Macpherson, Tara; Wright, Karen L. (Frontiers in Pharmacology, 2017)
The anti-cancer effect of the plant-derived cannabinoid, cannabidiol, has been widely demonstrated both in vivo and in vitro. However, this body of preclinical work has not been translated into clinical use. Key issues around this failure can be related to narrow dose effects, the cell model used and incomplete efficacy. A model of acute lymphoblastic disease, the Jurkat T cell line, has been used extensively to study the cannabinoid system in the immune system and cannabinoid-induced apoptosis. Using these cells, this study sought to investigate the outcome of those remaining viable cells post-treatment with cannabidiol, both in terms of cell size and tracking any subsequent recovery. The phosphorylation status of the mammalian Target of Rapamycin (mTOR) signalling pathway and the downstream target ribosomal protein S6, were measured. The ability of cannabidiol to exert its effect on cell viability was also evaluated in physiological oxygen conditions. Cannabidiol reduced cell viability incompletely, and slowed the cell cycle with fewer cells in the G2/M phase of the cell cycle. Cannabidiol reduced phosphorylation of mTOR, PKB and S6, pathways related to survival and cell size. The remaining population of viable cells that were cultured in nutrient rich conditions post treatment were able to proliferate, but did not recover to control cell numbers. However, the proportion of viable cells that were gated as small, increased in response to cannabidiol and normally-sized cells decreased. This proportion of small cells persisted in the recovery period and it did not return to basal levels. Finally, cells grown in 12% oxygen (physiological normoxia) were more resistant to cannabidiol. In conclusion, these results indicate that cannabidiol causes a reduction in cell size, which persists post-treatment. However, resistance to cannabidiol under physiological normoxia for these cells would imply that cannabidiol may not be useful in the clinic as an anti-leukemic agent.